Legal overview prior to the regulation of the cannabis trade in Mexico. - Icedo Paredes, Jesús Manuel (Posgrados de la División de Ciencias Económica Administrativas, 2022)
There are multiple questions relating to cannabis regulation in Mexico´s legal system in the approach of its legalization. Therefore, the event is analyzed with special interest in its marketing features. Therefore, it is necessary to anticipate the scenarios with a theoretical analysis of documentary sources based on legislative background; current legal standards; national jurisprudence; as well as doctrinal research from various fields. This is made to address possible considerations that might be adopted in the internal rule, compatible with the idiosyncrasy and internal legal institutions. Hence, the topic represents a hermeneutical space for research in its first phase. It is approached from a theoretical perspective, with the objective focused on outlining the potential legislative scenarios in order to subsequently propose a business model for the commercialization of a product with a prominent market, Cannabis, through the use of digital technologies, primarily, e-commerce.